(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
The ethics and aesthetics of a teacher are not just a set of rules and norms of behavior. This is a way of life, a worldview that determines the professional success of a teacher. Constant improvement in these areas allows the teacher to become not only a source of knowledge, but also a role model for his students.